APLIKASI TEKNOLOGI PEMBUATAN PUPUK ORGANIK PLUS UNTUK MENINGKATKAN PRODUKTIVITAS GAPOKTAN UMA DESA KABUPATEN - temaja, I.G.R.M.; Wirya, G.N.A.S.; Sumardani, N.L.G. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana Mengabdi, 2018)
The short course on organic fertilizer plus was held on Thursday, April 20, 2017 at Simantri 376. There are 32 members of Gapoktan Uma Desa participated in this program. The purpose of the short course is to provide knowledge, understanding and skill to members of Gapoktan about increasing productivity through the utilization of bali cattle dung as an organic fertilizer that has higher economic value. The problem solving method is to give theory and practice about formulating fermented organic fertilizer, Trichoderma on carrier media and organic fertilizer plus. During the delivery of theory and practice the participants' responses were very enthusiastic, so the discussion took place actively